An Analysis Upon Various Psychological and Physical Hazardous Work Faced By Children’S: a Review: Examining the Impact of Hazardous Work on Children's Health and Well-being (Journal of Advances and Scholarly Researches in Allied Education, 2016)
Child labour is a worldwidephenomenon but more focus is required on developing countries. The policyframework of International Labour Organization (ILO) to eliminate child labouris based on United Nations (UN) Declaration of Fundamental Principles andRights at work (1998). Over 170 million children worldwide still work in orderto sustain their basic needs. About 22000 working children die due tooccupational hazards every year, as per ILO estimates. Indian population hasmore than 17.5 million working children in different industries (Child Labourin India 1994; Tiwari 2005), and maximum are in agricultural sector, leatherindustry, mining and match making industries etc. As per provisions in theConstitution of India, “the State shall direct its policy towards protection ofchildhood and youth against exploitation and they shall not be employed to workin any factory or mine or engaged in any hazardous employment”; butunfortunately India has the largest number of urban and rural child workers inthe world (Fyfe, 1994)) India being a developing nation is faced withtraditional public health problems like communicable diseases, malnutrition,poor environmental sanitation and inadequate medical care. However,globalization and rapid industrial growth in the last few years has resulted inemergence of occupational health related issues. The major occupationaldiseases/morbidity of concern in India are silicosis, musculo-skeletalinjuries, coal workers’ pneumoconiosis, chronic obstructive lung diseases,asbestosis, by sinuses, pesticide poisoning and noise induced hearing loss.